Theranostic Role of Advanced Nanotechnological Tools in Early Brain Metastases in Lung Cancer: An Updated Review - Wu Y; Sun C; Jin K; Dong C (International Journal of Nanomedicine, 2025)
Yuanlin Wu,1,* Caiping Sun,2,* Ketao Jin,3 Changming Dong4 1Department of Thoracic Surgery, Shaoxing People’s Hospital, Shaoxing, Zhejiang, 312000, People’s Republic of China; 2Department of Medical Oncology, Shaoxing People’s Hospital, Shaoxing, Zhejiang, 312000, People’s Republic of China; 3Department of Colorectal and Anal Surgery, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, 310003, People’s Republic of China; 4Department of Neurosurgery, Shaoxing People’s Hospital, Shaoxing, Zhejiang, 312000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Changming Dong, Department of Neurosurgery, Shaoxing People’s Hospital, No. 568, Zhongxing North Road, Shaoxing, Zhejiang, 312000, People’s Republic of China, Email dcmdoc@126.com Ketao Jin, Department of Colorectal and Anal Surgery, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), No. 54, Youdian Road, Hangzhou, Zhejiang, 310003, People’s Republic of China, Email jinketao2001@zju.edu.cnAbstract: Lung cancer with brain metastases remains a clinical challenge and is often diagnosed at advanced stages when treatment options are limited. Nanotechnological tools have emerged as pivotal in enhancing both diagnostic and therapeutic approaches. Herein, we explore the theranostic potential of nanotechnology for the detection and treatment of lung cancer brain metastases, focusing on nanomaterials such as liposomes, polymeric nanoparticles, quantum dots, and magnetic nanoparticles, and their applications in imaging techniques like MRI, PET, fluorescence imaging, and CT. The role of nanotechnology in overcoming the blood-brain barrier and facilitating targeted drug delivery through passive and active targeting is also discussed. Additionally, it examines the application of nanocarriers in chemotherapy, radiotherapy, immunotherapy, and combination therapies. Special attention is given to immune-modulating nanoparticles, including checkpoint inhibitors and nano vaccines, as key innovations in immunotherapy. Theranostic nanoparticles are highlighted for their potential in real-time treatment monitoring. In summary, nanotechnological tools offer transformative potential in oncology, advancing diagnostics, enabling targeted therapies, and improving patient survival outcomes.Keywords: nanotechnology, brain metastases, lung cancer, theranostics, real-time monitoring, nanomaterials